PENGARUH BYSTANDER EFFECT DAN TEKANAN FINANSIAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (FRAUD) DI LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN MENGWI - Anak Agung Ayu Evy Putri Indraswari; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2022)
The tendency for accounting fraud to occur repeatedly is characterized by actions and policies to eliminate or hide actual information for manipulation purposes (Udayani, 2017). The purpose of this study is to determine the effect of the bystander effect and financial pressure on the tendency of accounting fraud in the LPD in Mengwi District. The population in this study were all LPD employees in Mengwi District, amounting to 306 people. The sample used was 169 employees who were determined by purposive sampling technique. The data analysis technique used in this research is multiple linear regression analysis using SPSS software. Based on the results of the research and discussion that have been described, it can be concluded that the bystander effect variable has a positive and significant effect on the tendency of accounting fraud in the LPD in Mengwi District. The financial pressure variable has a positive and significant effect on the tendency of accounting fraud in the LPD in Mengwi District